The Influence of Teacher Professionalism, Motivation, Attitude, and Culture on English Proficiency: Evidence from South Sulawesi, Indonesia - Asrifan, Andi; Cardoso, Luís Miguel Oliveira de Barros; Vivekanantharasa, Raveenthiran (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Proficiency in English serves as a crucial metric for assessing educational quality and employability in multilingual regions. In South Sulawesi, Indonesia, disparities persist due to variations in teacher professionalism, motivation, attitude, and cultural environment. This study investigates how these factors collectively influence students’ English proficiency. Data were gathered from 100 teachers and 300 students through surveys, interviews, and classroom observations using a mixed-methods design. Quantitative analysis revealed that teacher professionalism showed the strongest correlation with English proficiency (r = 0.65, β = 0.45), followed by teacher attitude (r = 0.60, β = 0.40) and motivation (r = 0.58, β = 0.38), while cultural influence had a moderate effect (r = 0.50, β = 0.30). Qualitative findings highlighted that limited professional development, insufficient institutional support, and strong local linguistic identity hindered teaching effectiveness, particularly in rural areas. The study emphasizes that enhancing teacher training, sustaining motivation, and applying culturally responsive pedagogies are vital for improving English outcomes. These insights provide practical guidance for policymakers and teacher education programs seeking to strengthen English instruction in multilingual educational settings.